Sistem Rekomendasi Desain Website Berdasarkan Tingkat Kemiripan Menggunakan Euclidean Distance - Cahyani Ainun Awaliyah; Agi Prasetyadi; Apri Junaidi (Research Group of Data Engineering, Faculty of Informatics, 2022)
The more internet users, the more interest in creating websites for certain purposes. To create a website that can attract visitors, a good website design is required. Website design is an important element in making a website, because the design of a website will create its own impression and image for website users. One of the technological developments is artificial intelligence, namely the Recommendation System which is a computer technology that is able to provide recommendations for the layman, in this study a website design recommendation system based on the Euclidean distance assessment resulted in a